An Extended Home Visit Programme Within the Swedish Child Healthcare System for First-Time Parents in Scania, Sweden: A Study Protocol - Elisabeth Mangrio; Lisa Hellström; Eva-Lotta Nilsson; Anna-Karin Ivert (Frontiers Media S.A., 2021)
Background: The Swedish Child Healthcare (CHC) system aims to provide equal and fair health care for all children and families in Sweden. Currently in Sweden, the CHC offers every family two home visits during the child's 1st year of life. During 2019, an extended home visit programme, called Grow Safely, was started in the region of Scania for first-time parents. The aim of the extended home visit programme was to provide support for first-time parents in order to improve the overall health of the child and family and contribute to better conditions for equal health. Instead of two home visits during the 1st year, a subsample of first-time parents would receive six visits during the child's first 15 months. These six visits would be conducted by CHC nurses and social workers, midwives, and dental assistants. In the present paper, we describe a research project related to the regional extended home visit programme; the project aims to illuminate the experiences of the participants and to investigate the perceived benefits of the programme in relation to improved health, social and emotional interaction between parent and child, and attitudes toward authorities and surrounding society.Method/Analysis: In order to evaluate the introduction of the intervention, three qualitative interview studies and one quantitative study with follow-up questionnaires will be conducted. Since the research project also comprises studies focusing on the implementation and expectations of politicians, civil servants, organizational managers, and professionals working within the programme, interviews within these fields will be conducted.Discussion: Sweden has a well-established CHC programme, but improvements are always possible. Previous research has shown that home visits are an effective tool to improve both the child's physical and mental health as well as the parents' well-being. However, this kind of intervention involves a significant investment from all organizations involved in the home visits; hence, it is important that the intervention is evaluated. The research project described in the present paper intends to examine the impact of the intervention, and its findings will aid decisionmakers in determining the future of the home visit programme.